2013
DOI: 10.1105/tpc.113.118620
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of FLOWERING LOCUS T by a MicroRNA in Brachypodium distachyon

Abstract: ORCID IDs: 0000-0003-4953-7258 (L.W.); 0000-0002-3377-4040 (L.M.).The highly conserved florigen gene FLOWERING LOCUS T (FT) functions at the core of the flowering pathways. Extensive studies have examined the transcriptional regulation of FT; however, other layers of FT regulation remain unclear. Here, we identified miR5200 a Pooideae-specific microRNA that is expressed in leaves and targets Brachypodium distachyon FT orthologs for mRNA cleavage. miR5200 was abundantly expressed in plants grown under short-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
94
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 87 publications
(99 citation statements)
references
References 67 publications
5
94
0
Order By: Relevance
“…We have shown that this FT homolog is not expressed in phyC mutants and that overexpression of this FT is able to rescue the delayed flowering phenotype of phyC. The closely related FT gene, FT2, can also promote flowering in Brachypodium (Wu et al 2013) and is also undetectable in the phyc background; thus, loss of FT2 expression might also contribute to the delayed flowering phenotype of the phyC mutant.…”
Section: Phyc Plays a Major Role In Photoperiodic Flowering In Pooidsmentioning
confidence: 99%
“…We have shown that this FT homolog is not expressed in phyC mutants and that overexpression of this FT is able to rescue the delayed flowering phenotype of phyC. The closely related FT gene, FT2, can also promote flowering in Brachypodium (Wu et al 2013) and is also undetectable in the phyc background; thus, loss of FT2 expression might also contribute to the delayed flowering phenotype of the phyC mutant.…”
Section: Phyc Plays a Major Role In Photoperiodic Flowering In Pooidsmentioning
confidence: 99%
“…Under LD, PPD1/PRR37 up-regulates FT1 in barley and wheat (25) but down-regulates FT homologs in rice and sorghum (58,59). Upregulation of FT1 in wheat is associated with the up-regulation of FT2 (43,71), which also promotes flowering (72). (Pathway B) PHYC also modulates the expression of circadian clock and clock output genes CO1 and CO2.…”
Section: Methodsmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are small endogenous, non‐coding regulatory RNA sequences that have key roles in regulation of gene expression in most of the eukaryotic cells. In plants, miRNAs regulate gene expression at both transcriptional and post‐transcriptional levels (Reinhart et al , Chapman et al , Ramachandran and Chen , Grant‐Downton et al ) and are involved in a number of physiological processes, such as growth, development and both biotic and abiotic stress responses (Mathieu et al , Wang et al , Grigorova et al , Thiebaut et al , Wu et al ). miRNAs have emerged as promising approaches for plant breeding applications, such as crop improvement strategies and genetic modification of agronomic traits (Meng et al , Liu and Chen ).…”
Section: Introductionmentioning
confidence: 99%